Responsibility of the Directorate General of Intellectual Property regarding The Passing Off Case Between Starbucks Coffee & Starbucks Cigarettes (Case Study 836 K/PDT.SUS-HKI/2022) - Simbolon, Alum; Vonny, Vonny (Universitas Islam Sultan Agung, 2024)
The aim of this research is to examine the responsibility of the Directorate General of Intellectual Property (DJKI) and to examine the considerations of the Panel of Judges regarding the brand passing off case between Starbucks Coffee and Starbucks Cigarettes based on Decision Number 836 K/Pdt.Sus-HKI/2022. DJKI's responsibility in cases of passing off brands has not been specifically regulated and written in a statutory regulation. However, DJKI has an obligation to comply with court decisions that have permanent legal force in brand cancellation lawsuits. Therefore, DJKI's responsibility for the case of brand passing off between Starbucks Coffee and Starbucks Cigarettes based on Decision Number 836 K/Pdt.Sus-HKI/2022 is to cancel the registration of the Starbucks Cigarette Brand with registration number IDM000342818 in class 34 owned by the Defendant, PT STTC from the Register Brand General. Furthermore, the considerations of the Panel of Judges in Decision Number 836 K/Pdt.Sus-HKI/2022 are in accordance with and were guided by Law No. 20 of 2016 concerning Brands and Geographical Indications. The Panel of Judges has determined PT STTC as the party found guilty of violating Article 21 section (1) letter c and Article 21 section (3) of the MIG Law as well as the Panel of Judges has also determined that the Starbucks brand owned by Starbucks Corporation is a well-known brand based on the criteria regulated in the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia No. 12 of 2021 concerning Trademark Registration.